Significados do trabalho para servidores técnicos e administrativos de uma instituição pública de ensino superior no interior paulista - Varge, Caroline Martins [UNESP] (2015)
The global context of political, economic, technological, and social changes affects directly work characteristics, mainly models of organization and management, and it brings consequences often harmful to workers. Therefore, studies about questions related to work are frequently required, in relation either with its contributions for societal development or with dangers leading to problems in workers' health, among other issues. It is also necessary to understand the presentation and relationship of workers in their work environment. In order to investigate these aspects related to work in public service, a quantitative and qualitative research was performed based on theoretical method approach in socio-historical Psychology. Its purpose was to know meanings of work for public administrative and technical employees of a higher education institution. The participants of this research are employees from four university units of Botucatu campus. Data collection was performed in two stages: the first one with collection of social and demographic characteristics of subjects, and the second one with questionnaire designed by the researcher, which was answered by 150 workers. Interviewed subjects had a positive concept of work, in overall and positive concept of public staff occupation, in particular. Meanings of being a public employee are described as satisfaction, social responsibility, work stability, contribution for the institution to achieve their goals, and aspects of work relationship. Such results suggest difference in the occupation of those public workers compared with the general situation of workers in the current social and economic context. It may benefit the preservation health at work. A following study deepening the knowledge of meanings of work for public employees is expected